VD_FINDINFO HC / 2013 / 416 vom 18. Juni 2013 - VD Tribunal cantonal (2013)
AUTORITÉ DE CONCILIATION, COMPÉTENCE RATIONE LOCI, DÉCISION D'IRRECEVABILITÉ, LITISPENDANCE | 18 CPC (CH), 201 CPC (CH), 319 let. a CPC (CH), 327 al. 3 let. a CPC (CH), 59 al. 2 let. b CPC (CH), 63 al. 1 CPC (CH)